(3TQM JNejS GdbUjOI GdTbQGWjSjI dCHj YHO Gddg eMeO GdeMLhHs - (3GdJhRQj, GHf GdTHGW, eMeO Hf Ydj Hf eMeO, J(B681(3g`s ((3YHO GddWja CMeO Hf GdTQjas)
(3ChdgG (B:s
(3aj GSe YHO GdeWdH Efg YGeQ aj bhd CHj bJjHI hYfO CHj ESMGb hZjQg ef LeghQ Cgd GdYde GSeg TjHI hgGTe GSeg YeQh hjbGd YeQh hGdYdG hYHO efGa GSeg GdeZjQIs
(3BNQgG (B:s
(3hgh GdYTj YfO ejd GdTeS ddZQhH hGUaQGQgG hRYe HYV GdfGS Cj CMd LeY CMjd hdG jUM dhLhOg jWhd PcQgG hGdUMjM Cfg daX eaQO eOdhdg heOdhd GdCMjd hGMOs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B681(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 283s
(3eYLe GdeDdajf(B: 3 / 544s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs